A proposed framework for implementing risk-based Shari'ah audit. Issue 3 (14th January 2021) - Sani, Suleiman Dalhatu; Abubakar, Mustapha
Abstract : Purpose: This paper aims to recommend a framework that serves as a practical work tool for conducting risk-based Shari'ah audit (RBSA) in Islamic financial institutions (IFIs). Design/methodology/approach: Qualitative research method was used through critical in-depth content analysis of documented literature to generate deep insights, further supported with a hypothetical illustrative case study application of the framework on an Islamic bank, aimed at bringing the framework to a practical, near real-life scenario. Findings: A robust RBSA framework has been developed which focuses on Shari'ah non-compliance risks to systematically and practically arrive at a rated opinion on the level of an IFI's adherence with Shari'ah rules and principles as recommended by the Accounting and Auditing Organization for Islamic Financial Institutions, aimed to safeguard the IFI and promote financial system stability at large. Research limitations/implications: Practical realities limited the study to the use of a hypothetical case study bank. Future researchers can apply the framework to a real case study of diverse IFIs for effective contextual recalibration in diverse jurisdictions. Practical implications: This paper aids the development of both internal and external Shari'ah audit practice using the risk-based approach. Social implications: The RBSA framework contributes to promoting public trust and confidence in the Islamic finance industry. Originality/value: This paper has proposed this RBSA framework as a practical work tool for Shari'ah auditors in their engagements and regulators in promoting sound governance and financial system stability. It provides foundation for future researchers in the field.